ANALISIS KANDUNGAN ASPARTAM YANG TERDAPAT PADA MINUMAN JAJANAN ANAK SEKOLAH YANG BEREDAR DI MAKASSAR DENGAN METODE HPLC - Seniwati Dali; A. Trihadi Kusuma; Afiat Wahyuni Anar (As-Syifaa Jurnal Farmasi, 2013)
This research have done of Aspartame compound in seven kinds of beverage of the student which turn in elementary school with tehe mean that to analyze Aspartame compound in beverage and have purpose to determine the concentration of Aspartame in beverage. As a comparison used the main of Aspartame with purity about 98,38%. The sample is weigh about 10 gram in a flask 50 ml, and then diluted with mobile phase is sodium dihydrogen phosphate and acetonitrile (82.5 : 17.5)ml and then it’s filtered by membrane filter 0,45 um. The result are sonicated and to injection about 20 ml to in colomn with rate of flow 1,2 mk/min and λ 210 nm. The sample is analyzed by HPLC method. The analyzed showed that the average concentration of Aspartame by calculating linear regression equation contained in the sample A. 7.5658 mg/kg, B. 198.3445 mg/kg, C. 257.8844 mg/kg, D. 226.5515 mg/kg, E. 0 mg/kg, F. 45.5389 mg/kg, G. 140.3748 mg/kg which is still below the standard of 600 mg/kg. So, sample E is just not contain of Aspartame. Key words : Aspartame, HPLC, Compound, Analyze